Steatocrit: A Simple Method for Detection Fat Malabsorption - Suharyono Suharyono; Hindra Irawan Satari; Agus Firmansyah (Indonesian Pediatric Society, 1992)
Steatocrlt was determined through microcentrifugation of fecal hemogenate from 45 patients with chronic diarrhoea. In the same patients urine materials were collected to determine fat malabsorption using Lipiodol absorption test. There were 28 male and 17 female patients. Severe malabsorption using steatocrit was detected tn 31 patients (68;9%), while LAT determined severe malabsorption in 34 patients (75.5%). The overall sensitivity was 88.2%, and spesificity was 90.9%. Nutritional status did not influence the sensitivity and spesificity of steatocrit. We propose that this simple semiquantitative test can be used as an alternative method for detecting fat malabsorption particularly in laboratories with limited technical expertise.